Duelo do imaginário na política sob a inspiração de Cornelius Castoriadis - Lima, José Eudes Silva de (2024)
This thesis addresses the issue of the duel of the imaginary in politics. The analysis will address moments in which Brazilian society makes its decisions, including the choice of vote, based on the manipulation of the collective imagination. Duels occur, especially, between reality and what is already culturally consecrated. Cornelius Castoriadis, with the work "The imaginary institution of society" is the philosophical inspiration for intellectual foundation. The main research base was articles from the mainstream national press between 2012 and 2022, especially up until the presidential election. The central problem is to raise political duels that society has fought, highlighting the role of art, reactionism, the economy and the agenda of customs. Based on the analysis of Tom Zé's song, "Don't have hatred in the summer", the text presents the importance of progressive sectors against hatred, manifested in multiple ways by far-right groups, inside and outside politics. The far-right uprising gained strength with the protests over the increase in bus fares in 2013 in the city of São Paulo, at the same time, under the force and sometimes anonymity of social media, anti-democratic agendas were legitimized, even if they are illegal. The duel of the imaginary in politics was able to elect and give voice to a leader who did not even have a government project and in his history had proposals such as killing 30 thousand people, closing the National Congress and establishing the return of the Dictatorship. The main conclusion of the thesis is that the economy is not an exclusive political determinant and that the customs already consolidated within the collective imagination have been decisive in recent periods